Safety and performance of a suprachoroidal sensor for telemetric measurement of intraocular pressure in the EYEMATE-SC trial. Issue 4 (12th November 2021) - Szurman, Peter; Mansouri, Kaweh; Dick, H. Burkhard; Mermoud, Andre; Hoffmann, Esther M; Mackert, Marc; Weinreb, Robert N; Rao, Harsha Laxmana; Seuthe, Anna-Maria
Abstract : Aim: To investigate the safety and performance of a telemetric suprachoroidal intraocular pressure (IOP) sensor (EYEMATE-SC) and the accuracy of its IOP measurements in open angle glaucoma (OAG) patients undergoing simultaneous non-penetrating glaucoma surgery (NPGS). Methods: Prospective, multicentre, open-label, single-arm, interventional clinical trial. Twenty-four eyes of 24 patients with OAG regularly scheduled for NPGS (canaloplasty or deep sclerectomy) were simultaneously implanted with an EYEMATE-SC sensor. Six-month follow-up on the sensor's safety and performance as well as on the level of agreement between the EYEMATE-SC measurements and IOP measurements with Goldmann applanation tonometry (GAT). Results: The eyes underwent canaloplasty (n=15) or deep sclerectomy (n=9) and achieved successful implantation of the sensor. No device migration, dislocation or serious device-related complications occurred. A total of 367 comparisons were included in the IOP agreement analysis. The overall mean difference between GAT and EYEMATE-SC measurements was 1.31 mm Hg (lower limit of agreement (LoA) 7.55 mm Hg; upper LoA –4.92 mm Hg). The maximum difference of 2.5 mm Hg ±3.96 (LoA 0.30–2.29) was reached on day 10 and continuously improved to an agreement of –0.15 mm Hg ±2.28 (LoA –1.24 to 0.89) after 6 months. Accordingly, the percentage of eyes within an IOP difference of ±5 mm Hg improved from 78% (day 3) to 100% (6 months). Conclusions: After 6 months, the EYEMATE-SC sensor was safe and well tolerated, and allowed continual IOP monitoring. Trial registration number: NCT03756662 .